A Discontinuous Pulse Width Modulation Method Based on a Current Angle for Driving Interior Permanent Magnet Synchronous Motor with Dead Time Compensation - 이옥형; 이형우; 이교범 (조명.전기설비학회논문지, 2025)
This paper presents a method for reducing switching losses and minimizing the harmonic distortion (THD) of the current in an interior permanent magnet synchronous motor (IPMSM) drive system by employing a phase current-based discontinuous pulse width modulation (DPWM) and a dead time compensation technique. Switching losses are effectively reduced by implementing a phase current-based DPWM. The phase current-based DPWM method is implemented by the offset voltage based on the phase angle of the current and clampsapppled to the switch where the absolute value of the phase current is maximized. Furthermore, the current polarity is identified based on the phase angle, allowing for the application of a dead time compensation voltage aligned with this polarity to mitigate voltage distortion induced by dead time. This technique effectively reduces the THD of the output current in a 2-level inverter operating an IPMSM. The integration of the phase current-based DPWM method with the dead time compensation method enhances the efficiency of the IPMSM drive system. The validity of the proposed method is verified by simulation and experimental results.
Keywords: Dead time compensation; DPWM; IPMSM; Switching loss reduction; Two-level inverter